Heterocellular Coupling Between Amacrine Cells and Ganglion Cells - Marc, Robert E.; Sigulinsky, Crystal Lynn; Pfeiffer, Rebecca L.; Emrich, Daniel; Anderson, James Russell; Jones, Bryan William (Frontiers in Neural Circuits, 2018)
All superclasses of retinal neurons, including bipolar cells (BCs), amacrine cells (ACs) and ganglion cells (GCs), display gap junctional coupling. However, coupling varies exten-sively by class. Heterocellular AC coupling is common in many mammalian GC classes. Yet, the topology and functions of coupling networks remains largely undefined. GCs are the least frequent superclass in the inner plexiform layer and the gap junctions mediating GC-to-AC coupling (GC::AC) are sparsely arrayed amidst large cohorts of homocellular AC::AC, BC::BC, GC::GC and heterocellular AC::BC gap junctions. Here, we report quan-titative coupling for identified GCs in retinal connectome 1 (RC1), a high resolution (2 nm) transmission electron microscopy-based volume of rabbit retina. These reveal that most GC gap junctions in RC1 are suboptical. GC classes lack direct cross-class homocellular coupling with other GCs, despite opportunities via direct membrane contact, while OFF alpha GCs and transient ON directionally selective (DS) GCs are strongly coupled to dis-tinct AC cohorts. Integrated small molecule immunocytochemistry identifies these as GA-BAergic ACs (γ+ACs). Multi-hop synaptic queries of RC1 connectome further profile these coupled γ+ACs. Notably, OFF alpha GCs couple to OFF γ+ACs and transient ON DS GCs couple to ON γ+ACs, including a large interstitial amacrine cell, revealing matched ON/OFF photic drive polarities within coupled networks. Furthermore, BC input to these γ+ACs is tightly matched to the GCs with which they couple. Evaluation of the coupled versus inhibitory targets of the γ+ACs reveals that in both ON and OFF coupled GC net-works these ACs are presynaptic to GC classes that are different than the classes with which they couple. These heterocellular coupling patterns provide a potential mecha-nism for an excited GC to indirectly inhibit nearby GCs of different classes. Similarly, coupled γ+ACs engaged in feedback networks can leverage additional gain of BC synap-ses in shaping the signaling of downstream targets based on their own selective coupling with GCs. A consequence of coupling is intercellular fluxes of small molecules. GC::AC coupling involves primarily γ+ cells, likely resulting in GABA diffusion into GCs. Survey-ing GABA signatures in the GC layer across diverse species suggests the majority of ver-tebrate retinas engage in GC::γ+AC coupling.